(untitled) (Journal of Pharmaceutical Negative Results, 2023)
BACKGROUND: Higher than recommended caesarean section (CS) rates may increase the risk of morbidity and mortality for both mother and child. Both advanced and developing nations have seen an increase in the number of CS delivery in recent years. The Robson categorization system splits all deliveries into ten groups that are mutually exclusive and entirely inclusive based on a set of preset obstetric features. Some of these include gestational age, parity, prior CS, the beginning of labour, fetal presentation, and the overall number of fetuses OBJECTIVE: To determine the rate of cesarean section, and evaluate perinatal outcome among women classified bases on Robson Classification. STUDY DESIGN: An analytical cross-sectional study PLACE AND DURATION: Hayatabad Medical complex Medical and Teaching Institute Peshawar Pakistan for a period of 03 years METHODOLOGY: All the women admitted to the hospital with pregnancy were included in the study. Data was collected from the files available in hospital record. The patients were classified in ten groups based on Robson Classification to evaluate the caesarian section rate and perinatal outcomes among groups. In addition, sociodemographic parameters such as age, place of residence, caesarean type, referral status, antenatal care, parity, gestational age, start of labour, fetal presentation and birth weight, indications for the caesarean section, as well as perinatal outcomes were noted. Data was entered and analyzed using SPSS version 24. RESULTS: The overall caesarian section rate in this study was 24.31%, the group 3 and 5 were major contributors for overall caesarian section cases, 15.38% women in the study went for elective caesarian section and rest of the 84.62% went for emergency caesarian section, 42.44 % neonates were admitted to the neonatal ICU, 34.7% were preterm and 29.41% were low birth weight, 157 perinatal mortalities were reported including NNM and still births. CONCLUSION: We evaluated the caesarian section rates in the groups based on Robson classification in our setting. Group 3- and 5 were was the leading contributor to the overall CS rate. This study also revealed the major perinatal outcomes among the groups.